2015
DOI: 10.1007/s11606-015-3204-y
|View full text |Cite
|
Sign up to set email alerts
|

Panel Management to Improve Smoking and Hypertension Outcomes by VA Primary Care Teams: A Cluster-Randomized Controlled Trial

Abstract: BACKGROUND: Panel Management can expand prevention and chronic illness management beyond the office visit, but there is limited evidence for its effectiveness or guidance on how best to incorporate it into practice. OBJECTIVE: We aimed to test the effectiveness of incorporating panel management into clinical practice by incorporating Panel Management Assistants (PMAs) into primary care teams with and without panel management education. DESIGN: We conducted an 8-month cluster-randomized controlled trial of pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In this issue, Schwartz et al 9 report on the effects of adding nonclinical staff to perform panel management in the care of patients with hypertension and/or who smoked. In an 8-month pragmatic cluster-randomized controlled trial at two Veterans Administration (VA) primary care sites, primary care teams in the intervention groups received either panel management assistant (PMA) support or PMA support plus targeted panel management education, while control providers received monthly lists of current smokers and patients with uncontrolled hypertension.…”
mentioning
confidence: 99%
“…In this issue, Schwartz et al 9 report on the effects of adding nonclinical staff to perform panel management in the care of patients with hypertension and/or who smoked. In an 8-month pragmatic cluster-randomized controlled trial at two Veterans Administration (VA) primary care sites, primary care teams in the intervention groups received either panel management assistant (PMA) support or PMA support plus targeted panel management education, while control providers received monthly lists of current smokers and patients with uncontrolled hypertension.…”
mentioning
confidence: 99%
“…In the prediabetes population, the 3-year DM incidence is estimated to be 15% (based on preliminary analysis of a similar NY VA cohort from 2010 to 2012, followed through 2015). A conservative estimate of the intracluster correlation coefficient (ICC) is 0.01, based on the median value found in a systematic review of cluster randomized trials [ 34 ] and the highest value calculated in our previous VA study [ 35 ]. This planned sample size will provide at least 80% power to detect an expected difference in annual hazard rates of time to DM incidence between two arms (3.5% per year in intervention vs. 5.4% per year in control), at a 0.05 significance level.…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by VA's Institutional Review Board and Research and Development Committee. Additional details on the study design and primary outcomes from the trial can be found elsewhere [40,41].…”
Section: Methodsmentioning
confidence: 99%